Tricot accepted as on-farm testing approach for official variety release in Nigeria: Two cassava varieties released through the tricot approach - 1000FARMS Platform; Teeken, Bela (2025)
This poster presents a success story from IITA’s work in Nigeria under the data collection activity of the 1000FARMS platform, led by the Alliance of Bioversity International and CIAT. It documents how participatory on-farm testing using the tricot approach contributed to the national Variety Release Committee’s decision to adopt farmer-generated evidence as part of the official cassava release process. By capturing farmer preferences and real-world performance at scale, this approach helped strengthen the relevance and inclusiveness of cassava breeding outcomes.